Practice to research: Integrating evidence-based practices with culture and context. (April 2015) - Weisner, Thomas S.; Cameron Hay, M.
There are ways to integrate culturally competent services (CCS) and evidence-based practices (EBP) which can improve the experiences of patients and their families and communities when faced with health problems, as well as the effectiveness and positive experiences of practitioners. CCS and EBP evidence should be jointly deployed for helping patients and clinicians. Partnership research models are useful for achieving the integration of CCS and EBP, since they involve close observation of and participation by clinicians and practitioners in the research process, and often use integrated qualitative and quantitative mixed methods. We illustrate this with 3 examples of work that can help integrate CCS and EBP: ongoing collection of information from patients, clinicians and staff, or "evidence farming"; close study and continuous improvement of activities and accommodations; and use of evidence of tacit, implicit cultural scripts and norms, such as being "productive, " as well as explicit scripts. From a research practice point of view, collaborative partnerships will likely produce research with culture and context bracketed in, and will contribute stronger research models, methods, and units of analysis.